Soil environmental factors shape the rhizosphere arbuscular mycorrhizal fungal communities in South African indigenous legumes (Fabaceae) - Afolakemi Alimi; Rasheed Adeleke; Annah Moteetee (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Alimi AA, Adeleke R, Moteetee A. 2021. Soil environmental factors shape the rhizosphere arbuscular mycorrhizal fungal communities in South African indigenous legumes (Fabaceae).Biodiversitas 22:2466-2476.The crucial role played by arbuscular mycorrhizalfungi (AMF) in the nutritional adaptation of plants tonutrient-deficientsoils is well recognized. However, little is known about the diversity of AM fungal communities in the rhizosphere of indigenous legumes of South Africa. This study presents the first morphological characterization of the AM fungal diversity present in the rhizosphere of eleven indigenous legume species fromtwo provinces in South Africa and correlates the diversity and community structure of AMF to soil physicochemical properties. Twenty AM fungal species belonging to ten genera were identified; Glomusand Acaulospora were the dominant genera, while Acaulospora colombiana, A. mellea, and Claroideoglomus etunicatumwere the prevalent species. The AM fungal spore density, diversity, andcommunity structurediffered markedly among the legume species in both provinces. Correlation and canonical correspondence analyses revealed that the diversity and spatial structure of AM fungal communitieswere significantly influenced by soil properties. This study providesa theoretical insight into the future potential of using the dominant AM fungal species as inoculants for sustainable management of legumes and indicated that soil factors are important environmental determinants of AM fungal diversity and community structure